Value co-creation, co-destruction, and firm performance: A proposed mediation of the internet of things - Ahmad Zaidi, Mohamad Faizal; Belal, H. M. (2018)
Value co-creation is a study on consumer-firm interactions, where consumers can be actively involved with firms in designing, developing, marketing, distributing, and (or) selling of products to personalize their service experiences. In contrast, value codestruction exists due to imbalance involvement between consumers and firm in cocreating of value as a result of misuse of resources.Previous studies have suggested while value co-creation will increase firm performance, value co-destruction will do just the opposite of that. In the meantime, the internet of things (IoT) has becoming important topic to study how value co-creation and co-destruction can be created. Therefore, it was expected the effects of value co-creation and co-destruction on firm performance can be better understood with IoT.However, study that has looked into the mediating effects of IoT in the relationships between value co-creation and co-destruction on firm performance in a single topic is still hard to find.In line with the research gap, this paper will be investigating the aforementioned issue by building a conceptual framework with research propositions.This paper is proposing that IoT will positively improve the effect of value co-creation on firm performance, while at the same time reducing the negative effect of value co-destruction.This paper is expected to enhance our knowledge on the relationships between value co-creation and co-destruction, improve our understanding on the effects of IoT on firm performance, and promotes resource-based view (RBV) to complement Service-Dominant (S-D) logic at explaining superior firm performance.